2009
DOI: 10.1253/circj.cj-08-0219
|View full text |Cite
|
Sign up to set email alerts
|

Complete Atrioventricular Block Associated With Takotsubo Cardiomyopathy

Abstract: Circ J 2009; 73: 589 -592 ransient left ventricular dysfunction with chest symptoms and electrocardiographic (ECG) changes mimicking those of acute myocardial infarction are known as takotsubo cardiomyopathy. [1][2][3] Although the pathogenesis of takotsubo cardiomyopathy remains unclear, physical or emotional stress is common and elevation of plasma catecholamines suggests that sympathetic stimulation plays a central role. When medical support is provided promptly, the long-term prognosis of takotsubo card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 8 publications
0
20
0
1
Order By: Relevance
“…Takotsubo cardiomyopahty often presents with abnormal findings on electrocardiography that mimic coronary artery disease and are occasionally complicated by various arrythmias (2,(6)(7)(8). Although the present patient did not exhibit typical ST-T changes or prolongation of the QT interval on the electrocardiograms, transient complete AV block was a complicating finding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Takotsubo cardiomyopahty often presents with abnormal findings on electrocardiography that mimic coronary artery disease and are occasionally complicated by various arrythmias (2,(6)(7)(8). Although the present patient did not exhibit typical ST-T changes or prolongation of the QT interval on the electrocardiograms, transient complete AV block was a complicating finding.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, syncope caused by complete AV block was observed in our emergency room. Several cases have been reported in which a permanent pacemaker was implanted due to bradyarrhythmia associated with Takotsubo cardiomyopathy that persisted even after improvements in left venticular wall motion (7,8). However, the AV block observed in the present case was transient, and the electrophysiological study performed on day 13 showed normal findings, indicating that the AV block was functional and permanent pacemaker implantation was not indicated.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of QT interval prolongation has been discussed in patients with Takotsubo cardiomyopathy (Abe et al, 2003, Desmet et al, 2003, Matsuoka et al, 2003, and there have been 17 reported cases of QT interval prolongation and torsades de pointes (TdP) associated with Takotsubo cardiomyopathy (Denney et al, 2005, Sasaki et al, 2006, Okada T, et al, 2007in Japanese], Nault et al, 2007, Boulouffe et al, 2007, Patel et al, 2007, Kurisu et al, 2008, Furushima et al, 2008, Hirose et al, 2008, Ghosh et al, 2009, Mahida et al, 2009, Inoue et al, 2009, Kawano et al, 2010, Purvis et al, 2009, Yamada et al, 2011 (Figure 2) (Table 1). Considering the 17 previous cases reported in the literature, QT prolongation in Takotsubo cardiomyopathy has been attributed to hypokalemia (n= 3), bradycardia associated with atrioventricular (AV) block (n=4), idiopathic long QT syndrome (n=2), hypokalemia plus antiarrhythmic therapy (n=1), and hypokalemia plus idiopathic long QT syndrome (n=1), hypokalemia and hypomagnesemia (n=1), hyponagnesemia (n=1), and antibiotic (n=1) in 14 cases, and there was no specific factor associated with QT prolongation in 3 cases.…”
Section: Torsades De Pointes In Takotsubo Cardiomyopathy With Qt Prolmentioning
confidence: 99%
“…Takotsubo cardiomyopathy-associated Torsades de Pointes has been reported in 2005 for the first time (Denney et al, 2005). We have reviewed this case report and additional 14 reports (Akashi et al, 2003;Boulouffe et al, 2007;Finsterer et al, 2007;Furushima et al, 2008;Ghosh et al, 2009;Hirose et al, 2008;Inoue et al, 2009;Kurisu et al, 2008;Mahida et al, 2009;Nault et al, 2007;Okada et al, 2007;Patel et al, 2007;Sasaki et al, 2006) concerning Takotsubo cardiomyopathy-associated Torsades de Pointes in 2009, and we have concluded that males with Takotsubo cardiomyopathy-associated QT interval prolongation are at risk for Takotsubo cardiomyopathy-associated Torsades de Pointes although most patients with Takotsubo cardiomyopathy are females. There has been a trend in the mean maximal QT interval being longer among patients with Takotsubo cardiomyopathy-associated Torsades de Pointes relative to patients with Takotsubo cardiomyopathy-associated QT interval prolongation.…”
Section: Introductionmentioning
confidence: 96%